The Urgency of Regulations on the Time Limit for Storing Notarial Protocols as State Archives - Adjie, Habib; Susanto, Aries Loren (Jurnal Hukum dan Keadilan, 2025)
A notarial protocol is a collection of documents that are considered State Archives and must be stored and maintained by the Notary in accordance with the provisions of applicable laws and regulations. Based on Article 15 paragraph (1), Article 16 paragraph (1) letter b, Article 58, Article 59, and Article 63 of the Notary Law (UUJN/UUJN-P), a Notary is responsible for storing the deeds and Notarial Protocols throughout their term of office, and these will be passed on to another Notary or their successor. The responsibility of the Notary holding the protocol is also to maintain the confidentiality of the personal data of the parties involved in legal actions reflected in the authentic deed. The lack of regulations governing the digital storage of the Notarial Protocol has created a legal gap. As a result, the digital storage of Notarial Protocols can only function as backup data